Exploration of sulfur in mixt anchor materials for lithium sulfur batteries. (11th October 2019) - Radhika, G; Subadevi, R; Sivakumar, M
Abstract: Lithium–sulfur (Li–S) batteries are drawing tremendous attention owing to high energy density, high theoretical capacity and high availability of sulfur. The practical application of Li–S batteries is retarded due to the dissolution of polysulfides and shuttle mechanism. With this backdrop, cyclic stability and Coulombic efficiency is demoted. In this regard, sulfur is loaded with three different materials such as metal oxide (MnO2 ) and carbon source of Acetylene Black (AB) and polymer Polyethylene glycol (PEG) which can be used as an electrode for Li–S batteries. The structural and morphological behavior has been analyzed by x-ray diffraction, Raman analysis and scanning electron microscopy. S/MnO2 composite delivers a discharge capacity of 1030 mAh g −1 in its initial cycle. S/MnO2 composite has a strong ability to adsorb the lithium polysulfides escalating the Coulombic efficiency.